2009
DOI: 10.2220/biomedres.30.235
|View full text |Cite
|
Sign up to set email alerts
|

The reciprocal relationship between heme oxygenase and nitric oxide synthase in the organs of lipopolysaccharide-treated rodents

Abstract: The production of nitric oxide (NO) by inducible NO synthase (NOS) and carbon monoxide (CO) by inducible heme oxygenase (HO) contributes greatly to endotoxemia. Reciprocal relationships have been proposed between the NO/NOS and CO/HO systems. However, the interaction between these systems during endotoxemia is unclear, and it is unknown whether the interactive behavior differs among organs. Using endotoxic rats, we studied the effects of the inducible NOS (iNOS) inhibitor L-canavanine (CAN), and the HO inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…This is supported by the fact that the decreases in NO levels were suggested to protect against LPS-induced endotoxaemia in rats (Crespo et al, 1999). Interestingly, even though a combined effect of p,p -DDT and LPS treatment on HO-1 expression was not supported by our findings, there is crosstalk between HO-1 and NOS2 induction, demonstrated by the fact that an HO inhibitor, zinc protoporphyrin, downregulates LPS-mediated HO-1 expression, leading to a further increase in NOS2 expression (Furuichi et al, 2009). Moreover, antiinflammatory and anti-apoptotic responses in p,p -DDT-treated livers suggests the expression of cytoprotective molecules, because such molecules have been previously found to be expressed in the liver of rats treated with various hepatic drug-enzyme inducers (Kobayashi et al, 2000;Reed et al, 2011).…”
Section: Discussioncontrasting
confidence: 64%
“…This is supported by the fact that the decreases in NO levels were suggested to protect against LPS-induced endotoxaemia in rats (Crespo et al, 1999). Interestingly, even though a combined effect of p,p -DDT and LPS treatment on HO-1 expression was not supported by our findings, there is crosstalk between HO-1 and NOS2 induction, demonstrated by the fact that an HO inhibitor, zinc protoporphyrin, downregulates LPS-mediated HO-1 expression, leading to a further increase in NOS2 expression (Furuichi et al, 2009). Moreover, antiinflammatory and anti-apoptotic responses in p,p -DDT-treated livers suggests the expression of cytoprotective molecules, because such molecules have been previously found to be expressed in the liver of rats treated with various hepatic drug-enzyme inducers (Kobayashi et al, 2000;Reed et al, 2011).…”
Section: Discussioncontrasting
confidence: 64%
“…The protective role of HO-1 has been demonstrated in experimental lung in LPS and CLP models [21,22]. We found that HO-1 acts as a potent antiinflammatory and antioxidant agent through its products CO and biliverdin.…”
Section: Discussionmentioning
confidence: 70%
“…This effect resulted from oxidative stress inhibition [35]. Additionally, the interaction between heme oxygenase and nitric oxide (NO) has already been observed in the kidney [36]. The HO-1 induction inhibits NO synthase [37], however fewer works have demonstrated the interaction between these systems in the kidneys of diabetic animals.…”
Section: Discussionmentioning
confidence: 99%